2020
DOI: 10.1186/s11671-020-03344-7
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-Related Nanoparticle Toxicity in the Biomedical Field

Abstract: The unique physicochemical characteristics of nanoparticles have recently gained increasing attention in a diverse set of applications, particularly in the biomedical field. However, concerns about the potential toxicological effects of nanoparticles remain, as they have a higher tendency to generate excessive amounts of reactive oxygen species (ROS). Due to the strong oxidation potential, the excess ROS induced by nanoparticles can result in the damage of biomolecules and organelle structures and lead to prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
268
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 467 publications
(275 citation statements)
references
References 209 publications
(120 reference statements)
5
268
1
1
Order By: Relevance
“…PEG is a neutral, hydrophilic and biocompatible polymer which improves the dispersion of NPs in water, it improves their bio-distribution and increases blood circulation time [ 30 ]. However, despite the PEG-coating and administration of a low dose of USPIONs, we found elevated production of the superoxide, which was increased in all tissues and organs investigated in this study, similarly as it was found using various types of NPs [ 31 ]. On the other hand, we were unable to unequivocally confirm elevated iron content in the tissues using the histochemical method.…”
Section: Discussionsupporting
confidence: 83%
“…PEG is a neutral, hydrophilic and biocompatible polymer which improves the dispersion of NPs in water, it improves their bio-distribution and increases blood circulation time [ 30 ]. However, despite the PEG-coating and administration of a low dose of USPIONs, we found elevated production of the superoxide, which was increased in all tissues and organs investigated in this study, similarly as it was found using various types of NPs [ 31 ]. On the other hand, we were unable to unequivocally confirm elevated iron content in the tissues using the histochemical method.…”
Section: Discussionsupporting
confidence: 83%
“…Intriguingly, we have also detected activation of necroptosis only in tumorigenic cells submitted to photooxidation damage. Necroptosis is triggered by perturbations of extracellular or intracellular homeostasis that critically depend on the kinase activities of RIPK1, at least in some settings, RIPK3, and consequent phosphorylation, oligomerization and migration of MLKL (mixed lineage kinase domain-like protein) to the plasma membrane 3,48 . MLKL oligomers form channels on the plasma membrane, leading to high osmotic pressure, water influx, release of intracellular components, and eventual plasma membrane rupture 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our data have provided molecular mechanisms behind a hitherto unexplored therapeutic approach, which have simultaneously activated alternative tumor regulated cell death pathways while preserving the integrity of most of the non-tumorigenic cells. This fact is of fundamental importance since despite all the recent technological improvements, breast cancer still has significantly impacts on global health, being disease recurrence and metastasis the bottleneck for an effective clinical treatment 2,3 . This study contributes to a better understanding of breast cancer susceptibility to photooxidation-induced damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations